Historiografi Korupsi di Indonesia: Resensi Buku Korupsi dalam Silang Sejarah Indonesia - Miftakhuddin Miftakhuddin (Rihlah : Jurnal Sejarah dan Kebudayaan, 2019)
This review aims to describe the contents of the book, analyze how the book reaches its objectives, and how the author's perspective in presenting his arguments and ideas. The review was conducted by using the report method proposed by Bond (1964). Overall, this book has three weaknesses. Firstly, Carey's writings were not well-translated, so it might complicate nonscholar readers. Secondly, discussion in the first two chapters strays from the topic of "corruption". Thirdly, this book tends to more like an anthology book (it does not seem unified). However, each chapter was written objectively and comparably. In terms of the organization of its ideas, the script of Margana and Carey appears to have been written in strict rules of historical research, both heuristics, criticism, interpretation, and historiography. Moreover, in Chapter IV, the construct has written in investigative writing by former journalist, Haryadi. It will make the readers' reasoning skills more analytical, critical and anticipatory. In conclusion, this book is a worthy reference for everyone who concerns on corruption issues in Indonesia, mainly due to its incisive analysis by experts and historians.Review ini bertujuan mendeskripsikan konten buku, menganalisis bagaimana buku mencapai tujuannya, dan bagaimana perspektif penulis dalam menyajikan argumen dan gagasannya. Review dituliskan dengan report method yang diusulkan Bond (1964). Secara keseluruhan, buku ini mempunyai tiga kelemahan. Pertama, tulisan Carey tidak diterjemahkan dengan baik, sehingga mungkin akan menyulitkan pembaca umum. Kedua, pembicaraan di dua bab pertama menyimpang terlalu jauh dari “korupsi”. Ketiga, buku ini lebih seperti buku antologi, sehingga terkesan tidak menyatu. Namun demikian, setiap bab dalam buku ini ditulis secara objektif dan berimbang. Ditinjau dari organisasi ide pokoknya, teks dari Margana dan Carey tampak ditulis mengikuti kaidah riset sejarah secara ketat, baik heuristik, kritik, interpretasi, maupun historiografi. Terlebih lagi pada Bab IV yang ditulis dengan nuansa investigatif oleh mantan wartawan Haryadi, akan membuat daya nalar pembaca menjadi lebih analitis, kritis, dan antisipatif.